Symbolic self-determination: the case of Malaysia and Australia's indigenous education policy - Rosnon, Mohd Roslan; Abu Talib, Mansor; Dahamat Azam, Mohamad Naqiuddin (Penerbit Universiti Sains Malaysia, 2021)
The United Nations Declaration on the Rights of Indigenous Peoples (UNDRIP) outlines the right to self-determination for indigenous peoples. To what extent this right to self determination is practised in Malaysia and Australia is the focus of this study. Therefore, this article examines to what degree indigenous peoples’ rights to self-determination are encompassed in the formulation and development of indigenous education policy that has been recognised and supported. In-depth interviews were conducted with 24 respondents consisting of policy makers, educators, and non-governmental organisations (NGOs) personnel in Malaysia and Australia, including indigenous scholars. The findings show that Australia’s Aboriginal and Torres Strait Islander people were more actively involved in charting their educational policies than indigenous peoples in Malaysia. Among Malaysia’s Orang Asli, there was limited negotiation as a facilitating component of self-determination and there was also limited recognition of indigenous rights in determining education policy.